Evaluating the Regular Sharaf Learning Program at the Foundation of Islamic and Arabic Language Learning In Indonesia - Asbarin, Asbarin; Nailil Amalia, Nabila; Mukhlishoh, Mukhlishoh (Institut Agama Islam Negeri Palangka Raya, 2024)
This research aims to scrutinize and assess the learning dynamics within the regular Sharaf learning program conducted by the Islamic and Arabic Learning Foundation. Employing a descriptive qualitative approach, data for this study were obtained through interviews with the program director, supervisors, and administrators. Data collection involved observation, interviews, and document analysis. Data analysis followed Miles and Huberman's framework, comprising data collection, reduction, presentation, and drawing conclusions. Findings indicate that the regular Sharaf learning program features effective teaching methods, sequential curriculum delivery, adequate instructional materials, and proficient instructors. The researchers aspire that this study contributes to advancing the management of Arabic language programs and facilitates the development of comprehensive Arabic language activities for enhanced outcomes.